1991
DOI: 10.1113/jphysiol.1991.sp018536
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for reflex upper airway dilator muscle activation by sudden negative airway pressure in man.

Abstract: SUMMARY1. To determine if negative upper airway pressure causes reflex pharyngeal dilator muscle activation, we used intra-oral bipolar surface electrodes to record genioglossus electromyogram (EMG) activity in response to 500 ms duration pressure stimuli of 0. -25.-5.-15, -25 and -35 cmH2O (0-90 % rise time < 30 ms) in ten normal, conscious, supine subjects.2. WN&ith the subjects relaxed at end-expiration, stimuli were applied in each of three conditions: (i) glottis open (GO), (ii) glottis closed (GC) and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
210
3
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(231 citation statements)
references
References 20 publications
10
210
3
3
Order By: Relevance
“…One such mechanism is the genioglossus negative pressure reflex, whereby the muscle is activated in response to rapid changes in negative intrapharyngeal pressure (i.e., pressures that are subatmospheric or suction pressure) (23). Consistent with the nature of OSA being a state-related disease, the genioglossus negative pressure reflex has been shown to be diminished during non-REM sleep in healthy individuals (24,25).…”
Section: Upper Airway Dilator Muscle Activity and Reflex Responsivenessmentioning
confidence: 81%
“…One such mechanism is the genioglossus negative pressure reflex, whereby the muscle is activated in response to rapid changes in negative intrapharyngeal pressure (i.e., pressures that are subatmospheric or suction pressure) (23). Consistent with the nature of OSA being a state-related disease, the genioglossus negative pressure reflex has been shown to be diminished during non-REM sleep in healthy individuals (24,25).…”
Section: Upper Airway Dilator Muscle Activity and Reflex Responsivenessmentioning
confidence: 81%
“…It was also shown that genioglossus muscle responds to negative airway pressure by reflex activation during wakefulness [75]. This reflex activation is reduced or lost during NREM sleep [76].…”
Section: Interaction Between Central and Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Já na expiração, ocorre a ativação tônica (contínua) mantendo assim, a espessura e tamanho da VAS. [42] A pressão negativa na faringe estimula as fibras proprioceptivas e aumenta sua resposta de ativação [43] Durante momentos de hipóxia e hipercapnia a ativação do genioglosso é aumentada. [44] Os músculos palatoglosso e palatofaríngeo aumentam sua ativação em respostas a breve pulsos de pressões negativas ou resistência inspiratória.…”
Section: Fatores Neuromuscularesunclassified